Notions of Teachers in Vocational Education about Purposefulness - Jurgena, Inese; Cedere, Dagnija; Grase, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
One of the strategic aims in the development of vocational schools is teachers’ purposeful professional activity. The aim of the article is to analyse notions of teachers of vocational schools about the importance of purposefulness in the life activity of pedagogues. Different research methods are used in the article: analysis of research literature, teachers’ surveys. The study resulted in finding out the factors promoting purposefulness: the necessity to achieve the aim, the apprehension and setting of the aim, the selection of means for attaining the aim, application of the means corresponding to the situation leading to the achievement of the aim and implementation of a concrete action plan. The authors conclude that there exists the interconnection between teachers’ purposefulness and the formation of learners’ purposefulness.